Correction: Drought trends projection under future climate change scenarios for Iran region. - Maryam Bayatvarkeshi; Monzur Alam Imteaz; Ozgur Kisi; Mohammad Farahani; Mohammad Ghabaei; Ahmed Mohammed Sami Al-Janabi; Bassim Mohammed Hashim; Baqer Al-Ramadan; Zaher Mundher Yaseen (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0290698.].